Job Satisfaction among Malaysian Pharmacists - Sivakami Janahiraman,; Thomas Paraidathathu, (penerbit ukm, 2007)
This study was carried out to gauge the level of job satisfaction among pharmacists in Malaysia. Surveys forms developed after referring to published studies, were mailed to 1700 pharmacist. Analysis of responses from 405 respondents revealed significant differences in job satisfaction with age, position held and monthly salary. Pharmacist within the age group of 26 to 35 were less satisfied with their work as compared to the other pharmacist. A monthly salary of more than RM8000 and prospects of promotion within an organization contributed to a high level of satisfaction among pharmacist. Sector of work and length of service did not appear to influence job satisfaction. Further analysis indicated that motivator factors and hygiene factors had a significant influence on job satisfaction, whereas job stress contributed toward dissatisfaction at work. The results of the study supported Herzberg’s theory, which states the motivator factors were far more important than hygiene factors in providing job satisfaction. From this study, it appeared that more than 50% of the pharmacists who responded had at least a moderate level of job satisfaction. However, efforts can be taken by employers to further improve job satisfaction among Malaysian pharmacists.